2020
DOI: 10.32479/ijefi.9063
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Sustainability of Small and Medium Enterprises in Oman: A Conceptual Framework

Abstract: This paper provides insights on the sustainability of small and medium enterprises (SMEs) in Oman and presents a conceptual framework for the government support to the SMEs. The paper adopted a sequential mixed method of interviews and structured questionnaire including 390 SMEs. Non-parametric techniques of Chi-square test and spearman rank correlation were used. The challenges facing SMEs in Oman include: The rules and regulations of doing business, the competition, and the lack of access to finance. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Most of the published studies in Oman's SMEs strongly agree about the challenges that affect SMEs' sustainability. Such as complicated rules and regulations, improper business planning, competition, lack of financial access, advisory, complex funding process, technological changes, customer interaction, weak entrepreneurial and workforce skills and knowledge (AL-Zakwani and M. S. K., 2019; Ramachandran and Yahmadi, 2019, Al-Shandoodi et al, 2019, Alqassabi, 2020. The different studies indirectly proved the impact of SC risks and uncertainties on the sustainability of Oman's SMEs, the researcher divides them into internal and external SC effects.…”
Section: Sc Risks and Uncertainties And Its Effect On Sustainability ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the published studies in Oman's SMEs strongly agree about the challenges that affect SMEs' sustainability. Such as complicated rules and regulations, improper business planning, competition, lack of financial access, advisory, complex funding process, technological changes, customer interaction, weak entrepreneurial and workforce skills and knowledge (AL-Zakwani and M. S. K., 2019; Ramachandran and Yahmadi, 2019, Al-Shandoodi et al, 2019, Alqassabi, 2020. The different studies indirectly proved the impact of SC risks and uncertainties on the sustainability of Oman's SMEs, the researcher divides them into internal and external SC effects.…”
Section: Sc Risks and Uncertainties And Its Effect On Sustainability ...mentioning
confidence: 99%
“…Arguably, government rules and regulations, competition, financial access, advisory, funding process, technological changes, economic crises, and customer's experience all are the external SC impacts on the sustainability of SMEs, as the various studies around Oman proved. Alqassabi (2020) found that the owners of SMEs admitted rules and regulations, competition, lack of financial access, customer interaction, and technology changes 'respectively' have a significant impact on the sustainability of their business. The study also cited that incubator plays a substantial role in enhancing Oman's SMEs' sustainability.…”
Section: Sc Risks and Uncertainties And Its Effect On Sustainability ...mentioning
confidence: 99%
See 3 more Smart Citations